2017
DOI: 10.2174/1745017901713010027
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and Risk of Post-Operative Cognitive Dysfunction (POCD): A Systematic Review and Meta-Analysis

Abstract: Background:Post-operative cognitive dysfunction (POCD) occurs frequently after major surgery. Hypertension is well-established as a risk factor for age-related cognitive impairment, but it is unclear whether or not it also increases the risk of POCD.Objective:To evaluate the role of hypertension in POCD risk in a systematic review and meta-analysis.Method:PubMed, Ovid SP and the Cochrane Database of Systematic Reviews were searched for longitudinal studies of adults undergoing surgery with reporting of hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 84 publications
3
18
1
4
Order By: Relevance
“…Hypertension and obesity were not independently associated with risk of POCD. These findings extend our previous meta-analyses which, largely based on unadjusted results of exploratory studies, had found significant associations for diabetes but not for obesity or hypertension with POCD risk [7, 8, 10]. …”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Hypertension and obesity were not independently associated with risk of POCD. These findings extend our previous meta-analyses which, largely based on unadjusted results of exploratory studies, had found significant associations for diabetes but not for obesity or hypertension with POCD risk [7, 8, 10]. …”
Section: Discussionsupporting
confidence: 89%
“…However, we did not see any significant influence of a prior history of hypertension on risk of POCD that was independent of its link to diabetes. The null finding suggests that vascular damage as a consequence of hypertension may only play a minor role in POCD development and replicates results of our meta-analysis of hypertension as a candidate risk factor for POCD [10]. Though we did not assess severity of hypertension which may be important in cognitive risk prediction [48], our finding warrants further enquiry particularly in view of established associations of this risk factor with cognitive impairment per se [15, 49, 50].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…There is substantial variation in the number and types of neuropsychological tests that have been used in POCD research, however [6]. This hampers comparability between studies and may account for inconsistent results in POCD incidence [7] and epidemiology [8]. Specifically, a priori evaluation of their psychometric properties including their stability over time as measured by test-retest reliability in relevant control samples is rarely considered in test selection.…”
Section: Introductionmentioning
confidence: 99%